The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/catal10121404
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Catalytic Chemoenzymatic Tandem Reaction for the Synthesis of Natural Stilbenes in Continuous Flow

Abstract: In view of the development of efficient processes for the synthesis of high-value compounds, the combination of bio- and chemocatalysis is highly promising. In addition, implementation of immobilized catalysts into continuous setups allows a straightforward separation of the target compound from the reaction mixture and ensures uniform product quality. In this work, we report the optimization of a chemoenzymatic tandem reaction in continuous flow and its extended application for the synthesis of pharmacologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Some months later, the same authors reported the use of a 3D printed continuous stirred tank reactor that allowed an increase in the substrate concentration, and therefore of the productivity since the overall conversion was around 15% for the same reaction . Fine-tuning of the reaction conditions of the original report, and extension to other iodoaryl substrates allowed the synthesis of different stilbenes in 32–54% conversion under similar conditions …”
Section: Metal–enzyme Cascades Using Individual Catalystsmentioning
confidence: 99%
“…Some months later, the same authors reported the use of a 3D printed continuous stirred tank reactor that allowed an increase in the substrate concentration, and therefore of the productivity since the overall conversion was around 15% for the same reaction . Fine-tuning of the reaction conditions of the original report, and extension to other iodoaryl substrates allowed the synthesis of different stilbenes in 32–54% conversion under similar conditions …”
Section: Metal–enzyme Cascades Using Individual Catalystsmentioning
confidence: 99%
“…Decarboxylation by encapsulated B. subtilis phenolic acid decarboxylase (PAD) was followed by a Heck coupling of the resultant vinylphenol to an aryl iodide. Resveratrol and methoxy- and dehydroxylated analogues 48 could be generated in 33–62% yield on a 1 mol scale in just 1 h. 55 …”
Section: Polyphenolsmentioning
confidence: 99%
“…The output was connected to a collection bottle, as shown in Scheme 1. Columns with the same internal diameter and different lengths (2, 10, 15 cm) were also filled with AR-35, following the same procedure described above, and studied in subsequent tests [42,43] (Figure 3). Initially, 1.0 M solutions of HCB 1a (20 mL) and 1.0 M thiol 2a (20 mL) were fluxed with high flow rates, resulting in low conversions of the corresponding adduct 3a (entry 1), Table 2.…”
Section: Entrymentioning
confidence: 99%